The use of computer simulations on grade eleven learners' performance in plants biodiversity, Mankweng Circuit - Bodirwa, Kgashane Bethuel (My University, 2020)
Learners’ performance largely depends on the pedagogy used. This study explored the use of Computer Simulations (CS) to teach plants biodiversity to grade eleven learners Mankweng Circuit. A randomised Solomon Four-Group design was used. Sixty-six learners from two schools equipped with computers were randomly assigned to the Experimental Group (EG), and 66 learners from two other schools without computers were the Control Group (CG). A performance pre- and post-test was used to the EG taught using CS and to the CG taught using Chalk-and-Talk Method (CTM). Also, Focus Group Discussion Interviews (FGDI) were conducted with 12 learners: six from each of the EG and the CG to collect information regarding their attitudes towards the methods used to learn biodiversity. The quantitative data were analysed using a T-test and Analysis of Variance (ANOVA), while the qualitative data were analysed thematically. The results show that the learners in the EG performed better than those in the CG (T-test; p < 0.05), (ANOVA; p < 0.05). Hypothesis one which states that learners in the EG who were taught using CS will perform better than those in the CG taught using CTM is accepted. Also, hypothesis two, which states that learners’ performance in the pretest will not vary in the EG and the CG is accepted. Also, hypothesis three which states that there will be no statistically significant differences in achievements between boys and girls in the EG is established. Thus, the CS method is a useful tool to enhance learners’ performance. Keywords: Computer simulations, PCK, TPACK, Quasi-experiment, Solomon four group design, Learner’s performance
Thesis (M. Ed. (Science Education)) -- University of Limpopo, 2020
Keywords: Computer simulations; PCK; TPACK; Quasi-experiment; Solomon four group design; Learner’s performance; COLTS (Computer program language); Academic achievement; Children's literature in science education